Down-regulated microRNA-141 facilitates osteoblast activity and inhibits osteoclast activity to ameliorate osteonecrosis of the femoral head via up-regulating TGF-β2. Issue 7 (2nd April 2020) - Tian, Lei; Sun, Shui; Li, Wei; Yuan, Lin; Wang, Xianquan
ABSTRACT: Osteonecrosis of the femoral head (ONFH) is a pathological process that initially occurs in the weight-bearing field of the femoral head. Due to the unknown pathogenesis, this study was for the investigation of the effect of microRNA-141 (miR-141) targeting transforming growth factor-β2 (TGF-β2) on regulating osteoblast activity and osteoclast activity in steroid-induced ONFH. Tissues of ONFH and normal femoral head were collected for detecting the expression of miR-141 and TGF-β2. A rat model of ONFH was constructed by injection of hormones, and transfected with miR-141 inhibitors and overexpressed TGF-β2. The apoptosis of bone cells was detected by TUNEL staining. The expression of osteoprotegerin (OPG), osteoprotegerin ligand (OPGL), Bcl-2, Bax, Runx2, BMP2 and RANK were detected. Highly expressed miR-141 and lowly expressed TGF-β2 existed in femoral head tissues in ONFH. Inhibited miR-141 resulted in elevated TGF-β2 in femoral head tissues in ONFH of rats. Depressed miR-141 or overexpressed TGF-β2 inhibited the apoptosis of bone cells of rats with ONFH and induced elevated OPG, Bcl-2, BMP2, Runx2 and declined OPGL, Bax and RANK expression in the femoral head tissues of rats with ONFH. Altogether, we find that down-regulated miR-141 promotes osteoblast activity and inhibits osteoclast activity to ameliorate ONFH via up-regulated TGF-β2 expression.